Chemiresistive biosensors based on carbon nanotubes for label-free detection of DNA sequences derived from avian influenza virus H5N1 - Fu, Yangxi; Romay, Victor; Liu, Ye; Ibarlucea, Bergoi; Baraban, Larysa; Khavrus, Vyacheslav; Oswald, Steffen; Bachmatiuk, Alicja; Ibrahim, Imad; Ruemmeli, Mark; Gemming, Thomas; Bezugly, Viktor; et al. (Sensors and Actuators B-Chemical, 2017)
We developed chemiresistor-type biosensors based on carbon nanotubes for highly efficient and fast detection of avian influenza virus (AIV) subtype H5N1 DNA sequences. Semiconducting single-walled carbon nanotubes (sc-SWCNTs) or nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs) were used as two alternative active sensing elements, and their sensitivity to different concentrations of DNA target were compared. In these sensors long nanotubes (>5 μm) were placed between interdigitated metal electrodes so that individual nanotubes connect the electrodes. The nanotubes were functionalized with DNA probe sequences non-covalently attached to the sidewalls. Such functionalized-nanotube sensors could reliably detect complementary DNA target sequences of the AIV H5N1 with concentration ranging from 2 pM to 2 nM in 15 min and at room temperature. Our nanotube-based biosensors are small, flexible, disposable and easy-to-fabricate that makes them promising for point-of-care applications and clinical diagnostics.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Biosensor; Carbon nanotube; Chemiresistor; DNA; Hybridization